2018
DOI: 10.1002/pra2.2018.14505501002
|View full text |Cite
|
Sign up to set email alerts
|

Ascertaining the place of library & information science in knowledge management research

Abstract: In the past few years, many researchers and practitioners have shown the value of applying knowledge management (KM) in libraries and other information settings – so as to serve the patron better and to innovate services. However, it is unclear to what extent has mainstream KM literature embraced LIS research as a domain within KM. In this research, we seek to ascertain the place of the LIS field in KM journals by analysing what the top KM journals – as identified by Google Scholar – have published on LIS in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…While there have been many studies conducted on KM in libraries and many more are currently being conducted, we do not know the extent to which KM forms a part of LIS research. In a previous study (Agarwal and Islam, 2018), the authors tried to ascertain the place of LIS in KM research. We found that only 1.8% of all articles in the top ten KM journals published since the year 2000 related to LIS.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been many studies conducted on KM in libraries and many more are currently being conducted, we do not know the extent to which KM forms a part of LIS research. In a previous study (Agarwal and Islam, 2018), the authors tried to ascertain the place of LIS in KM research. We found that only 1.8% of all articles in the top ten KM journals published since the year 2000 related to LIS.…”
Section: Introductionmentioning
confidence: 99%
“…These are all important areas when implementing KM within libraries and other information settings. The overall findings of this study revealed that KM has comparatively high visibility (3.84%) in the LIS field, as opposed to LIS within the KM field, where Agarwal and Islam ()’s study demonstrated a visibility of only 1.8%. Thus, LIS journals engage with KM more oftenthan KM journals engage with LIS.…”
Section: Discussionmentioning
confidence: 57%
“…While there have been many studies conducted on KM in libraries, we do not know the extent to which knowledge management forms a part of LIS research. Agarwal and Islam () tried to ascertain the place of LIS in KM research and found that only 1.8 % of all articles in the top ten KM journals published since the year 2000 related to LIS. In this paper, we take an opposite lens and investigate the place of KM in LIS research.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Under the current economic system reform and continuous social development, modern people's mental health problems have become more prominent (Vitale, 2016), which may lead to the exhaustion from work and study, and even the symptoms of anxiety and depression (Sinnasamy & Karim, 2014). Whereas, good mental health state can improve individual enthusiasm for work, study, and life (Agarwal & Islam, 2018). Librarians are likely to have mental health problems because of Hebei University of Science and Technology, Shijiazhuang 050018, China E-Mail: 1054918522@qq.com high workloads etc.…”
Section: Introductionmentioning
confidence: 99%